A Pre-Experimental Study to Assess the Effectiveness of Abdominal Effleurage on Labor Pain Intensity Among Primipara Mothers During 1st Stage of Labor in Selected Hospitals of Distt. Mohali, Punjab (Part 2) - Kaur, Harpreet; Gurjar, Santosh Kumar (Universal Research Reports, 2023)
Childbirth is considered to be one of the crucial events in a woman’s life. Treating pain is important because coping with pain influences the birthing experiences as is the most excruciating pain that every mother has to bear while giving birth. The role of the health care provider is to handle the parturient with immense care. With this aim, the study was conducted to evaluate the effectiveness of abdominal effleurage on labor pain intensity among primipara mothers during 1st stage of labor in selected hospitals of Distt. Mohali, Punjab. Quantitative approach with a Pre Experimental One Group Pre-test Posttest Research Design was used. By using non-probability purposive sampling technique, 25 primipara mothers undergoing 1st stage of labor were selected from Doctor Square Multispeciality Hospital, Mohali, Punjab in the month of June 2023. Data was collected by using the Numeric Pain Rating Scale (NPRS), Likert scale to assess the level satisfaction of primipara mother after abdominal effleurage and Structured Record analysis Performa for maternal and fetal outcome. Findings of the study revealed that majority 8 (32%) primipara mothers were between age group of 26-29 years, 24 (96%) primipara mothers belong to Hindu religion, 11 (44%) primipara mothers were married, 13 (52%) had secondary education, 12 (48%) worked as private employees, 15 (60%) belonged to urban area and 17 (68%) were between 37-38 weeks of gestation.